Identification and Characterization of a Nonimmunoglobulin Factor in Human Saliva That Inhibits Streptococcus mutans Glucosyltransferase - Jespersgaard, Christina (American Society for Microbiology, 2002)
Saliva contains an array of nonimmunoglobulin defense factors which are thought to contribute to the protection of the hard and soft tissue surfaces of the oral cavity by modulating microbial colonization and metabolism. Here we report the discovery of a putative innate defense factor in human saliva that inhibits the glucosyltransferase (GTF) of Streptococcus mutans, a virulence enzyme involved in oral colonization by this pathogen. The GTF-inhibiting factor (GIF) was initially identified as a nonimmunoglobulin salivary component that interfered with detection of antibodies to the glucan-binding region (GLU) of GTF by an enzyme-linked immunosorbent assay. This inhibitory activity was present in whole saliva and submandibular-sublingual saliva, but it was essentially absent from parotid saliva. GIF inhibited the recognition of S. mutans cell surface-associated GTF by specific antibodies but had no effect on antibodies to other cell surface antigens, suggesting that GIF specifically binds to GTF on S. mutans. GIF purified by size exclusion or affinity chromatography was used for biochemical and functional characterization. Analysis of GIF by sodium dodecyl sulfate-polyacrylamide gel electrophoresis revealed a high-molecular-weight glycoprotein after staining with Coomassie blue or Schiff's reagent. Heating and reduction with 2-mercaptoethanol of GIF resulted in the release of a ∼58-kDa protein that was identified as α-amylase by Western blotting using anti-α-amylase antibodies. GLU bound blotted α-amylase, suggesting that the latter molecule is the GLU-binding component of the GIF complex. The ability of GTF to synthesize extracellular glucans was inhibited by GIF but not by uncomplexed α-amylase or an unrelated high-molecular-weight glycoprotein. In conclusion, our findings demonstrate that in human saliva, there is a high-molecular-weight glycoprotein-α-amylase complex which is capable of inhibiting GTF and may contribute to control of S. mutans colonization in the oral cavity.